Особливості семантичної параметризації української фітомеліоративної термінології у спеціальних словниках кінця ХХ – початку ХХІ ст. - Петрова, Тетяна; Petrova, Тetіаna (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано термінологію фітомеліорації, зокрема опрацьовано лексикографічний опис базового терміна фітомеліорація; визначено та схарактеризовано родо-видові відношення; досліджено багатозначність у термінології; установлено омогрупи, одиниці яких є міжсистемними омонімами; представлено класи- фікацію особливостей синонімії та її моделі.In the article the terminology of phytoamelioration is analyzed, the peculiarities of its dictionary representation, including processed lexicographic description of basic term of phytoamelioration, are revealed; the polysemy in terminology are studied; the intersystem paronyms are fixed; the homogroups, the units of which are intersystem homonyms, are installed; the problem of functioning of synonyms in phytoameliorative terminology is studied, the classification of peculiarities of synonymy and its models are presented; the genus-species relations are characterized and the most used types of models of their construction, which is the highest estimate of phytoameliorative terminology as a system, are defined.
Peculiarities of Semantic Parameterization of Ukrainian Phytoameliorative Terminology in Special Dictionaries the end of XX century – the Beginning of the XXI Century
Keywords: термін; термінологія; терміносистема; фітомеліоративна термінологія; галузевий словник; the term; terminology; termsystem; phytoameliorative terminology; branch dictionary